Intervención de enfermería en paciente adolescente de 13 años de edad con colelitiasis - Baño Flores, Luisa María (2020)
Cholelithiasis is a disease in which the accumulation of hardened deposits of digestive fluid in the gallbladder occurs, it is rare in children and adolescents, although its prevalence is increasing due to factors such as hemolytic disorders, obesity, family history of gallstones, cystic fibrosis, etc. The predominant stones in children are pigmentary and one of the established factors is the existence of hemolysis. Cholesterol stones are usually detected in adolescence and there is an increase in cases in girls. We present the case of a 13-year-old adolescent patient with cholelithiasis, who came to the emergency room due to pain in the right upper quadrant with 8 days of evolution that intensifies on palpation, nausea, sweating, diarrhea and general malaise. According to scientific and practical standards, the patient has been implemented the nursing care process, applying appropriate interventions according to their needs, with the aim of restoring their health and reintegrating them into society.